Examining the relationship between transformational leadership and employee empowerment / Nabila Huda Ibrahim, Tuan Nooriani Tuan Ismail, and Mahadir Ladisma @ Awis - Ibrahim, Nabila Huda; Tuan Ismail, Tuan Nooriani; Ladisma @ Awis, Mahadir (Universiti Teknologi MARA, Shah Alam, 2017)
Transformational leadership is a leadership style that has been used to increase the followers’ performance and it has been proven by many studies as effective leadership in increasing organizational effectiveness. One of the significant outcomes of transformational leadership is the employee empowerment. The employee empowerment shows that the employees have authorities over their jobs as well as enhancing their in decision making. The empowerment of employee is one of the ways for a company to increase it’s efficiency. This is because the empowered employees are able to find opportunities and solve problems by their own. This paper presents the study on the relationship between transformational leadership and the employee empowerment. A cross-sectional survey is has been done with the total of 113 employees from the selected banks in Kuala Terengganu. The correlation analysis was used to determine the relationship between transformational leadership and the employee empowerment. The result indicates a significant relationship between transformational leadership and employee empowerment